2001
DOI: 10.1089/10445470152611982
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Myocardial Tissue Damage During Transmyocardial Laser Revascularization with the CO2Heart Laser®

Abstract: CO2 laser TMR does not result in significant injury to the myocardium. Cardiac enzymes play an important role in the detection of perioperative myocardial infarction in TMR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…An absence of correlation between the peak enzyme levels and the number of laser/sham channels has been shown in previous clinical studies [19,20]. Our study showed that this lack of relation was the same for troponin.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…An absence of correlation between the peak enzyme levels and the number of laser/sham channels has been shown in previous clinical studies [19,20]. Our study showed that this lack of relation was the same for troponin.…”
Section: Discussionsupporting
confidence: 67%
“…This may explain some of the differences of the results. Cardiac enzymes have also been evaluated after transmyocardial laser revascularization [19,20,24]. In one study [20], CK values were higher after laser than after coronary by-pass grafting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations